2014
DOI: 10.15835/nsb649464
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effects of Benzyladenine and <i>meta</i>-Topolin on Sweet Basil (<i>Ocimum basilicum</i>) Micropropagation

Abstract: Micropropagation of aromatic plants reveals an effective way of obtaining high volume, virus-free plant material of uniform quality. The application of meta-Topolin (mT) (N6-(2-hydroxybenzyl) adenine-9-riboside) and aromatic cytokinin as Benzyladenine (BAP) in the micro propagation of sweet basil (Ocimum basilicum L.) was tested for the first time and plant growth parameters assessed to determine the optimum level of these cytokinins. Additionally, the rate of root-growth inhibition due to these two cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…For two species of the Prunus genus, cultures grown on medium with a hydroxylated benzylaminopurine derivative had twice as much fresh weight than those on a medium supplemented with BAP [27]. Although the effect of m-T on the propagation of sage species has not been described, it was found to stimulate the proliferation of two other species of Lamiaceae, Ocimum basilicum [28] and Dracocephalum forrestii, [29] and improve the morphology of the shoot culture. Of three concentrations of m-T used in our study, 1 mg/L was found to be most effective.…”
Section: Discussionmentioning
confidence: 96%
“…For two species of the Prunus genus, cultures grown on medium with a hydroxylated benzylaminopurine derivative had twice as much fresh weight than those on a medium supplemented with BAP [27]. Although the effect of m-T on the propagation of sage species has not been described, it was found to stimulate the proliferation of two other species of Lamiaceae, Ocimum basilicum [28] and Dracocephalum forrestii, [29] and improve the morphology of the shoot culture. Of three concentrations of m-T used in our study, 1 mg/L was found to be most effective.…”
Section: Discussionmentioning
confidence: 96%
“…BA is the most commonly used cytokinin for micropropagation, but plant taxa differ in their preference towards specific cytokinins. Recently, meta-Topolin (mT) has become a more common cytokinin in the in vitro plant production (Werbrouck et al 1996;Gentile et al 2014;Koszeghi et al 2014). In certain species gibberellic acid (GA 3 ) may also induce the formation of axillary shoots (George et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of 8.2 µM mT had a positive effect-the percentage of regenerated plants was higher than of those growing with 8.2 µM BA [36]. Kőszeghi et al [13] compared the effects of the mT and benzyladenine on shoot regeneration in common basil (Olicimum basilicum). Out of the five variants, each with a different concentration of mT in the MS medium, that using 1 mg•L −1 produced the highest number of shoots.…”
Section: Discussionmentioning
confidence: 99%
“…Growth regulators commonly used in in vitro plant propagation are cytokinins. They are applied during the proliferation stage to produce as many axillary buds, and hence microcuttings, as possible [13]. Cytokinins play an important role in regulating different aspects of plant growth and development: they stimulate cell divisions, delay aging of leaves and flower development, define defensive mechanisms helping the plant to adapt to different stressors [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation